Economic Aspects of Transportation Activities - Perić, Teodor; Malić, Alana; Kujundžić, Ante (Promet - Traffic&Transportation, 2012)
The function of transport is to bridge the distance betweenthe producer and the consumer at the lowest possible price. Anyway in which transport costs can be reduced has to be welcomed,either through introduction of a means which correspondsclosely to the needs of transport service users (more convenient,safer, more reliable, faster transport), or a meanswhich is less expensive to provide, and its function regardingeconomic aspect can also be efficient and reliable.